Association between anthropometric measurements and dental caries in Turkish school children - Köksal, Eda; Tekçiçek, Meryem; Yalçin, Siddika Songül; Tuğrul, Belma; Yalçin, Suzan; Pekcan, Gülden (Central European journal of public health, 2011)
AIM: To evaluate the association between anthropometric measurements and dental caries in school children. METHODS: The study was conducted on 245 primary school children (50.2% boys, 49.8% girls,), aged 5 to 9 years. The prevalence and severity of dental caries was measured using the decayed, missing or filled surfaces (dmfs, DMFS) and teeth (dmft, DMFT) indices. RESULTS: Mean dmft indices in children for boys and girls were 5.5 +/- 3.92 and 5.0 +/- 3.64, respectively. The prevalence of children with dental caries (dmft > or = 1) was 84.9%. The prevalence of children with body mass index (BMI) <-1SD and > or = +1SD was 15.9% and 22.9%, respectively. Dental caries were found in 89.7% of children with low body weight (including underweight and at risk for underweight) and in 66.1% of overweight-obese children (p<0.05). Similarly, high indices were detected significantly more often in children with low body weight (p<0.05). Height, weight, BMI and percent of fat mass were found to be negatively correlated with dmft indices (r:-0.141, p: 0.028; r:-0.171, p: 0.007; r:-0.139, p: 0.030; r:-0.158, p: 0.013, respectively). CONCLUSION: Children with low body weight have a higher risk of developing dental caries than overweight-obese children. For these reasons, the evaluation of nutritional status in children should be implemented in control programs for dental caries both on the community and individual levels.
Keywords: Surveys and Questionnaires; Anthropometry; antropometrie; Dental Caries; Humans; index tělesné hmotnosti; Body Mass Index; Overweight; dítě; DMF Index; Child; Schools; Female; rizikové faktory; lidé; Turecko; Thinness; průzkumy a dotazníky; předškolní dítě; zubní kaz; ženské pohlaví; Male; školy; Turkey; Cross-Sectional Studies; hubenost; mužské pohlaví; Child, Preschool; průřezové studie; nadváha; Risk Factors